PENGARUH TINGKAT KONSERVATISME PELAPORAN KEUANGAN PADA KEADAAN SEBELUM ROTASI AUDIT (PRE-ROTATION) DAN SETELAH ROTASI AUDIT (POST-ROTATION) DENGAN DISKRESIONER MODEL JONES - Any Dewi (Ma Chung Press, 2016)
In this research, Researcher investigated the changes in managerial discretion over financial reporting following the Audit Rotation KMK No. 243/06/2002. We documented that an increasing in conservatism in financial reporting is followed by Audit Rotation and the result is require for Public Accountant and Public Accountant Office (PAO) to limit audit tenure. First, researcher found that forms report lower discretionary accruals after audit rotation than in period preceding audit rotation. Second, the researcher was made additional investigation for sure, and the result says similar that firms reported lower discretionary accruals after audit rotation.These result are obtained with measurement using regression analysis and independent sample t-test statistic. The formula is adopted from discretionary accruals Jones Model and Modified Jones Model. The Empirical evidence is supported decision from the goverment to require mandatory audit rotation KMK no. 243/06/2002.